Implementing a data warehouse : a methodology that worked - Ullrey, Bruce Russell (Authorhouse, 2007)
The purpose of this book is to document the methodology and chronology of work activity used to successfully implement a data warehouse. Each step of the methodology is presented in the book, often using actual working documents as examples. The book contains lessons learned (both good and bad) as well as measures of success for each step. Again, the purpose of this book is to provide actual examples of processes, work papers, technical documentation, pitfalls and measures of success that led to a successful working data warehouse. This is not "The BEST and ONLY Book" for implementing a data warehouse and associated BI, but if a reader wants to see a methodology that worked - this book will provide that view